Teori Pengambilan Keputusan Pada UMKM Nyidam Duren Kertabumi - Dita Novia Hidayat; Fahra Nurarsyifah; Intan Nur Zakiah; Mirah Sekar Arum; Ujang Suherman (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study discusses the theory of decision-making applied in the management of MSMEs, focusing on a case study of MSME Nyiidam Duren Kertabumi which is facing a crisis and almost going bankrupt. The right decision-making process is very important for business continuity, especially in situations full of uncertainty. This study aims to explore the obstacles faced by MSMEs in managing the workforce and identify decision-making steps that can be taken to save the business. Based on direct interviews with business managers, it was identified that one of the main obstacles was the inability of the workforce to meet company expectations. This study also analyzes the decision-making style and process used in dealing with the crisis, and provides recommendations for strategic steps that can be taken to improve business conditions. The results of this study indicate that rational and participatory decision-making, with a focus on workforce training, performance evaluation, and the application of digital technology, can be an effective solution in facing existing challenges.